2021
DOI: 10.1097/j.jcrs.0000000000000631
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of crystalline lens tilt and decentration and associated factors in age-related cataract

Abstract: Approximately 10% of cataract patients have a tilt of 7 degrees or greater and decentration of 0.4 mm or greater. Axial length, front curvature radius, lens thickness, and age correlate with tilt and decentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…The presence of postoperative complications was also recorded. IOL tilt and decentration were measured and calculated automatically with swept-source anterior segment optical coherence tomography (SS-ASOCT, CASIA2; Tomey Corp., Nagoya, Japan) under the mode of a 3-dimensional (3D) scan at the last visit under mydriatic conditions using a mixture of 0.5% tropicamide and 0.5% phenylephrine hydrochloride (Mydrin-P, Santen Pharmaceutical, Osaka, Japan) according to the method previously described ( 9 , 10 ). Briefly, CASIA2 uses a swept-source laser with a 1,310-nm wavelength at a frequency of 0.3 s and provides higher resolution images of IOLs.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of postoperative complications was also recorded. IOL tilt and decentration were measured and calculated automatically with swept-source anterior segment optical coherence tomography (SS-ASOCT, CASIA2; Tomey Corp., Nagoya, Japan) under the mode of a 3-dimensional (3D) scan at the last visit under mydriatic conditions using a mixture of 0.5% tropicamide and 0.5% phenylephrine hydrochloride (Mydrin-P, Santen Pharmaceutical, Osaka, Japan) according to the method previously described ( 9 , 10 ). Briefly, CASIA2 uses a swept-source laser with a 1,310-nm wavelength at a frequency of 0.3 s and provides higher resolution images of IOLs.…”
Section: Methodsmentioning
confidence: 99%
“…Previous study has investigated the effects of capsulorhexis size and shape on the tilt and decentration of IOLs that a larger capsulorhexis size with bad coverage of the IOL edge is significantly correlated with IOL decentration. 22 In this study, the circularity index of FLACS was more precise than that of CPS, and the area and perimeter was more stable, which indicates a bettersized capsulotomy. The data of IOL decentration verify that a more precise capsulotomy in the femtosecond case leads to a better-centered IOL.…”
Section: Discussionmentioning
confidence: 48%
“…In patients with age-related cataract, Chen et al's study has reported that shorter AL contributed to larger crystalline lens tilt. 12 Wang et al's study has elaborated that AL ≥30 mm was a risk factor for clinically significant IOL decentration in patients with high myopia. 5 Our previous studies also showed that short AL was associated with a greater IOL tilt, whereas longer AL was highly associated with IOL decentration.…”
Section: Discussionmentioning
confidence: 99%